MITIGATION IN THE SEXUAL VIOLENCE PONDOK PESANTREN SINGOSARI ISHLAHIYAH CAMPAIGNS SOCIAL MEDIA-BASED DIGITAL LITERACY - Fiaji, Noveria Anggraeni (Wisesa: Jurnal Pengabdian Masyarakat, 2022)
Al Ishlahiyah Islamic Boarding School is the oldest Islamic boarding school in Singosari with a curriculum that is getting better every year. However, there is no mention of sexual education in the curriculum, even though cases of sexual violence don’t rule out the possibility of occurring in Islamic boarding schools. Based on the description of the situation analysis, the problems faced by partners are 1) a Low understanding of students on acts of sexual violence that may have been experienced by students, and 2) there has been no sexual violence mitigation training in Islamic boarding schools and on campuses. Based on the problems, several solutions were formulated namely 1) preparing digital literacy designs for sexual mitigation of students, 2) increasing the competence (cognitive, affective, psychomotor) of students in mitigating sexual violence, and 3) evaluating sexual violence mitigation training through digital literacy. In according with the PBL principle, the digital literacy training syllabus is prepared in the stage of understanding cases of sexual violence that have occurred at the boarding school, 2) the stage of training in making public texts with the theme of sexual violence through digital literacy, 3) the stage of training content creation in the form of public texts as sexual violence mitigation education, and 4) the training stage for disseminating the results of public texts through campaigns on social media. From these activities, it can be seen that 1)an increase in participant's understanding regarding sexual violence, responsive pathways for handling sexual violence, prevention of sexual violence, and anti-sexual violence campaigns in Islamic boarding schools, 2) Islamic Boarding Schools established a crisis center Islamic Boarding school as a form of advocacy and partisanship of Islamic boarding School on prevention and treatment sexual violence in Islamic boarding schools, and 3) there is an agreement (MoU) to develop an anti-sexual violence discourse with UPT PKM UB.